The shunning - Lewis, Beverly (Minneapolis, Minnesota : Bethany House, 1997)
When Katie Lapp, an Amish woman from Hickory Hollow, Pennsylvania, stumbles across a satin infant gown in her parents' attic, it leads to a devastating confession from her parents that completely changes her life.
Keywords: Amish -- Fiction; Religious fiction